A study to determine factors contributing to lack of established oral rehydration therapy corners in lusaka urban clinics - Bwalya, Edith Mwaanga (Lusaka: University of Zambia , School of Medicine, 1994)
The purpose of the study was to determine factors contributing to lack of establishment of ORT corners in Lusaka. urban health centres inspite of the training of health workers on the same. The data was collected from 50 health workers and was done between 1st and 31st of August 1994.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Oral rehydration therapy for children --Zambia.; Diarrhea in children --Zambia.